Is there a determining factor that predicts mortality in patients with congenital diaphragmatic hernia? - Gunendi, Tansel; Erginel, Basak; Bastu, Ercan; Kalelioglu, Ibrahim; Has, Recep; Soysal, Feryal Gun; Keskin, Erbug; Celik, Aladdin; Salman, Tansu (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2017)
Aim: This study was designed to investigate the factors affecting the prognosis in neonates with congenital diaphragmatic hernia (CDH) who were treated in our clinic. These factors included prenatal lung-head ratio (LHR), prenatal stomach and liver presence in the thorax, blood gases in the first 24 h and the modified ventilation index (MVI). Material and methods: The study was carried out retrospectively in 30 neonates with prenatally diagnosed left CDH who were treated in our clinic between January 2007 and 2013. Data were collected, evaluated, and statistically analyzed for gender, birth weight, gestational age, prenatal LHR, prenatal presence of stomach and liver in the thorax, postnatal initial blood gases in the first 24 h and MVI. Results : The median LHR for non-survivors was 1.49 and for survivors 1.51. No statistically significant difference in LHR was detected between survivors and non-survivors. In 19 neonates, prenatal ultrasonography (USG) revealed intrathoracic stomach, and 9 of these infants died. Intrathoracic liver was seen in 15 neonates, and 9 of these died. A statistically significant difference was not found between survivors and non-survivors in the intrathoracic liver or intrathoracic stomach neonates. A comparison between the non-survivors and survivors showed a median pH value of 7.10 in non-survivors and 7.24 in survivors (p = 0.002). The median PaCO2 value was 69.4 mm Hg in non-survivors and 51.9 mm Hg in survivors (p = 0.01). There were statistically significant differences in pH and PaCO2 values. The median value of MVI was 33 in survivors and 100 in non-survivors. There was a statistically significant difference between overall non-survivors and survivors in the MVI value (p < 0.05). Conclusions : Based on the findings, postnatal pH, and PaCO2 and MVI values are favorable prognostic factors in CDH in our selected group of patients.